Binder-free freestanding flexible Si nanoparticle–multi-walled carbon nanotube composite paper anodes for high energy Li-ion batteries - Yao, Kang; Zheng, Jim P.; Liang, Zhiyong (Journal of materials research, 2018)
Si nanoparticles and multi-walled carbon nanotubes (MWNTs) were combined using the simple, inexpensive, and scalable approach involving ultrasonication and positive-pressure filtration to generate binder-free freestanding flexible Si–MWNT (Si–MW) composite paper anodes for Li-ion batteries. Through controlling the Si/carbon nanotube (CNT) weight ratio, the composite with 3:2 Si/CNT ratio exhibited the optimal balance between the high capacity of SiNPs and high conductivity and structural stabilization quality of MWNTs, leading to high rate capability as well as specific capacity and cyclability surpassing the conventional slurry-cast SiNP electrode using binder and current collector and other complicated freestanding Si/carbon composite designs. After 100 cycles, our electrode retained a capacity of 1170 mA h/g at 100 mA/g and 750 mA h/g at 500 mA/g. Moreover, a different electrolyte composition enabled a reversible capacity of 1300 mA h/g at 100 mA/g after 100 cycles. The freestanding feature of our electrodes is promising for enhanced energy density of Li-ion cells.